Intestinal P Glycoprotein Acts as a Natural Defense Mechanism against Listeria monocytogenes - Neudeck, Brien L. (American Society for Microbiology, 2004)
Mechanisms by which the intestinal epithelium resists invasion by food-borne pathogens such as Listeria monocytogenes are an evolving area of research. Intestinal P glycoprotein is well known to limit the absorption of xenobiotics and is believed to act as a cytotoxic defense mechanism. The aim of this study was to determine if intestinal P glycoprotein is involved in host defense against L. monocytogenes. Caco-2 cells and a P-glycoprotein-overexpressing subclone (Caco-2/MDR) were employed in addition to mdr1a(−/−) mice and wild-type controls. In vitro invasion assays and in vivo experiments were employed to measure bacterial invasion and dissemination. In addition, L. monocytogenes proteins were labeled with [(35)S]methionine, and the transepithelial transport across Caco-2 monolayers was characterized in both directions. Overexpression of P glycoprotein in Caco-2/MDR cells led to increased resistance to L. monocytogenes invasion, whereas P-glycoprotein inhibition led to increased invasion. Flux of [(35)S]methionine-labeled L. monocytogenes proteins was significantly greater in the basolateral-to-apical direction than in the apical-to-basolateral direction, indicating dependence on an apically located efflux transporter. Moreover, inhibiting P glycoprotein reduced the basolateral-to-apical flux of the proteins. Early dissemination of L. monocytogenes from the gastrointestinal tract was significantly greater in the mdr1a(−/−) mice than in wild-type controls. Expression and function of intestinal P glycoprotein is an important determinant in resistance to early invasion of L. monocytogenes.